Leveraging Digital Platforms to enhance knowledge of livelihoods professionals to integrate Health and Nutrition agenda in livelihoods platform - Swati (2023)
This PowerPoint presentation was given during the Delivering for Nutrition in South Asia Conference, November 1, 2023.